COVID-19 prevention and control measures and experiences during the 14th National Games of China: a qualitative interview study - Li, Nan; Hou, Shike; Zhang, Yongzhong; Yao, Lulu; Li, Tiantian (Frontiers in Public Health, 2024)
Background: The 14 th National Games was the first sporting mass gathering to be held in China in the context of the COVID-19 pandemic. It may increase the risk of severe acute respiratory syndrome coronavirus 2 transmission. In order to reduce the spread of the virus during the 14th National Games, the Chinese government took a series of public health measures, and ultimately no confirmed cases were found in the 14th National Games venues.Objective: This study aimed to discuss preventive and control measures used to respond to the COVID-19 pandemic during the 14 th National Games.Methods: Five experts were selected for this study using a snowball sampling method, and semistructured and in-depth interviews were conducted. Based on grounded theory, the transcriptions were analysed and coded using Nvivo 12 software.Results: A theoretical model of the COVID-19 prevention and control measures at the 14 th National Games of China was constructed. The model contains seven main components: the health risks of mass gatherings, crowd management, emergency medical care, allocation of emergency medical resources, pandemic emergency drills, the pandemic prevention and control management platform (Quanyuntong app), and emergency response plans.The study showed that the deployment of emergency medical resources was the most important for mass gatherings. This study not only expanded the applications of grounded theory but also serves as a reference for future scholars when conducting more in-depth empirical studies on public health countermeasures for mass gatherings and can inform organizers when holding mass gatherings.